Introduction to business analysis and valuation - Palepu, Krishna G., 1954-; Bernard, Victor L.; Healy, Paul M. (Cincinnati, Ohio : South-Western College, 1997)
This book is divided into five parts: Introduction; Business analysis tools; Business analysis applications; Cases in financial statement analysis; and Compaq computer corporation.
Keywords: Finance; Business enterprises; Business enterprises -- Valuation; Financial statements; Business enterprises -- Valuation -- Case studies